Tin soldering paste capable of reducing voidage by adding iodine element and preparation method of tin soldering paste

By adding iodine element additives to the solder paste, the problem of high cavitation rate during welding is solved, and the effect of reducing cavitation rate and avoiding harmful gases is achieved, reducing equipment costs and improving environmental protection.

CN119407395APending Publication Date: 2025-02-11DONGGUAN YONGAN TECH

Patent Information

Application Number
CN202411642158.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Existing solder paste is prone to hollows during soldering, resulting in a decrease in the mechanical properties of the solder joints and may produce harmful gases that are not conducive to the environment.

Method used

By adding 0.1% to 2% of the iodine element additive to the solder paste, the surface tension of the solder paste is reduced, the wetting effect is improved, and the gas diffusion and escape speed is accelerated, thereby reducing the cavity rate.

Benefits of technology

It effectively reduces the void rate of solder paste, avoids the need for using a special vacuum furnace, reduces equipment costs, and does not generate harmful gases, which is environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005138753130000021
    Figure BDA0005138753130000021
  • Figure BDA0005138753130000041
    Figure BDA0005138753130000041
  • Figure BDA0005138753130000061
    Figure BDA0005138753130000061
Patent Text Reader

Abstract

The invention discloses soldering paste added with iodine and capable of reducing voidage and a preparation method of the soldering paste. The soldering paste is prepared from the following raw materials in percentage by mass: 85-90% of lead-free soldering powder; 9%-14% of a soldering flux; 0.1%-2% of an iodine element additive; the soldering flux is composed of the following raw materials in percentage by mass: 35%-45% of rosin; 8%-12% of a thixotropic agent; 8%-10% of an active agent; 2%-4% of an antioxidant; 2%-3% of a corrosion inhibitor; and the balance solvent. By adding the iodine additive with a specific content, the iodine additive can effectively reduce the surface tension of the soldering paste, improve the wetting effect and accelerate the diffusion and escape speed of gas, so that the purpose of reducing voidage is achieved, a special vacuum furnace is not needed, the equipment cost is effectively reduced, and the production efficiency is improved. And meanwhile, the product does not contain bromine or chlorine, so that harmful gas is not generated during welding, and the product is very environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of solder paste technology, in particular to a solder paste with iodine added to reduce void rate and a preparation method thereof. Background Art

[0002] The void phenomenon caused by SMT solder paste for reflow soldering cannot be eliminated in the industry for the time being. Domestic and foreign solder paste manufacturers have been committed to reducing the void rate. The appearance of voids will affect the mechanical properties of solder joints, deteriorate their strength and fatigue life, and the voids will grow with the long-term operation of solder joints. The growth of voids will cause the voids to combine together to form extended cracks and then cause solder joints to break. In addition, voids are also prone to overheating, reducing the reliability of solder joints. The main reason why voids are prone to overheating is the reduction of effective area of ​​heat conduction (heat dissipation). Generally speaking, the main causes of voids include: 1. Poor wetting caused by the shrinkage of solder during the solidification stage; 2. Outgassing of electroplating materials (mainly substrates) during welding; 3. The solder joint contains flux components. The mechanism of void generation is complex. The generally accepted view is: 1. The void rate decreases with the increase of solderability; 2. The voids decrease with the decrease of coverage area.

[0003] There are two measures to control voids: one is to use a dedicated vacuum furnace for welding, but this welding equipment is relatively expensive, resulting in high equipment costs, and general manufacturers cannot afford it; the other is to use a specific solder paste, the flux of which contains bromine or chlorine additives, but this solder paste will produce harmful gases when used for welding, which will damage the ozone layer and is very environmentally unfriendly. Therefore, it is necessary to study a solution to solve the above problems. Summary of the invention

[0004] In view of this, the present invention aims at the deficiencies of the prior art, and its main purpose is to provide a solder paste with iodine added to reduce the void rate and a preparation method thereof, which can effectively solve the problem that the existing solder paste will produce harmful gases during welding, resulting in environmental pollution.

[0005] To achieve the above purpose, the present invention adopts the following technical solutions:

[0006] A solder paste with iodine added to reduce void rate is composed of the following raw materials in percentage by weight:

[0007] Lead-free solder powder 85%~90%;

[0008] Flux 9%~14%;

[0009] Iodine additive 0.1% to 2%;

[0010] The soldering flux is composed of the following raw materials in percentage by mass:

[0011]

[0012] As a preferred solution, the lead-free solder powder is composed of four elements: tin, bismuth, silver and copper, wherein the bismuth content is 15% to 25%, the copper content is 0.5% to 1.2%, the silver content is 0.8% to 4.5%, and tin is the balance.

[0013] As a preferred embodiment, the iodine element additive is a mixture of one or more of potassium iodide, sodium iodide, ammonium iodide, lithium iodide, zinc iodide, silver iodide, and organic iodine compounds.

[0014] As a preferred solution, the rosin is a mixture of one or more of KHR-130 rosin crystal, AX-80 fully hydrogenated rosin, maleic acid modified rosin, RJH-145 polymerized rosin, and P-105 terpene resin.

[0015] As a preferred solution, the thixotropic agent is a mixture of one or more of modified hydrogenated castor oil, organic bentonite, and polyamide wax thixotropic agent.

[0016] As a preferred embodiment, the active agent is a mixture of one or more of succinic acid, glutaric acid, oxalic acid, phenylsuccinic acid, dodecanedioic acid, and decyltetradecanoic acid.

[0017] As a preferred embodiment, the antioxidant is a mixture of one or more of organic acid antioxidants, phenolic antioxidants, and thiol antioxidants.

[0018] As a preferred solution, the corrosion inhibitor is an organic corrosion inhibitor, an inorganic corrosion inhibitor or a composite corrosion inhibitor.

[0019] As a preferred embodiment, the solvent is a mixture of one or more of diethylene glycol hexyl ether, diethylene glycol dibutyl ether, diethylene glycol monobutyl ether, diethylene glycol monooctyl ether and tripropylene glycol butyl ether.

[0020] A method for preparing solder paste with iodine added to reduce void rate comprises the following steps:

[0021] (1) Weigh rosin, thixotropic agent, activator, antioxidant, corrosion inhibitor and solvent according to proportion;

[0022] (2) Add rosin, solvent and thixotropic agent into the same container, heat to 150°C to 170°C, and stir until completely melted;

[0023] (3) Cooling the above system to 120°C to 140°C, then adding the activator, antioxidant and corrosion inhibitor, and stirring until completely melted, cooling to obtain a paste flux, and storing it in a cold storage at 0 to 10°C for later use;

[0024] (4) Weigh lead-free solder powder, flux and iodine additive in proportion, pour into a vacuum mixer, stir at a low speed for 15 to 20 minutes, then fill with nitrogen and stir at a medium speed for 50 to 60 minutes to fully mix the lead-free solder powder, flux and iodine additive, then evacuate and stir at a medium speed for 10 to 15 minutes to obtain solder paste.

[0025] Compared with the prior art, the present invention has obvious advantages and beneficial effects. Specifically, it can be seen from the above technical solution that:

[0026] By adding a specific amount of iodine additives, the iodine additives can effectively reduce the surface tension of the solder paste, improve the wetting effect, and also accelerate the gas diffusion escape rate, thereby achieving the purpose of reducing the void rate. There is no need to use a dedicated vacuum furnace, which effectively reduces the equipment cost. At the same time, this product does not contain bromine or chlorine, and no harmful gases will be generated during welding, which is very environmentally friendly. DETAILED DESCRIPTION

[0027] The present invention discloses a solder paste with iodine added to reduce the void rate, which is composed of the following raw materials in percentage by mass:

[0028] Lead-free solder powder 85%~90%;

[0029] Flux 9%~14%;

[0030] Iodine additive 0.1% to 2%;

[0031] The soldering flux is composed of the following raw materials in percentage by mass:

[0032]

[0033] The lead-free solder powder is composed of four elements: tin, bismuth, silver and copper, wherein the bismuth content is 15% to 25%, the copper content is 0.5% to 1.2%, the silver content is 0.8% to 4.5%, and the tin content is the balance. The lead-free solder powder is ultrasonic atomized tin powder or centrifugal atomized tin powder, and the particle size range can be 10-15 μm. The iodine element additive is a mixture of one or more of potassium iodide, sodium iodide, ammonium iodide, lithium iodide, zinc iodide, silver iodide, and organic iodine compounds, which can effectively reduce the surface tension of the solder paste, improve the wetting effect, and also accelerate the gas diffusion escape velocity, thereby achieving the purpose of reducing the void rate. The rosin is a mixture of one or more of KHR-130 rosin crystal, AX-80 fully hydrogenated rosin, maleic acid modified rosin, RJH-145 polymerized rosin, and P-105 terpene resin. The thixotropic agent is a mixture of one or more of modified hydrogenated castor oil, organic bentonite, and polyamide wax thixotropic agent. The active agent is a mixture of one or more of succinic acid, glutaric acid, oxalic acid, phenylsuccinic acid, dodecanedioic acid, and decyltetradecanoic acid. The antioxidant is a mixture of one or more of organic acid antioxidants, phenolic antioxidants, and thiol antioxidants; wherein the organic acid antioxidant can react with the oxide on the surface of the solder, thereby removing the oxide and restoring the activity of the solder, and the organic acid antioxidant includes acetic acid, citric acid, etc.; the phenolic antioxidant is one of the key components of the solder antioxidant, which can effectively inhibit the oxidation reaction of the solder in the air and extend the service life of the solder. The phenolic antioxidant has high thermal stability and chemical stability and can maintain its antioxidant performance during the welding process; the thiol antioxidant can combine with the metal ions in the solder to form a stable compound, thereby preventing the oxidation of the solder. The corrosion inhibitor is an organic corrosion inhibitor, an inorganic corrosion inhibitor or a composite corrosion inhibitor; wherein the organic corrosion inhibitor can be benzotriazole (BTA), epoxy resin, fatty acid, phosphate ester, etc., which have excellent corrosion inhibition performance and a wide range of applications; inorganic corrosion inhibitors are represented by calcium, zinc, magnesium, etc., have high temperature corrosion resistance, and are suitable for high temperature and high pressure working environments; composite corrosion inhibitors are composed of organic and inorganic corrosion inhibitors, providing more comprehensive corrosion protection. The solvent is a mixture of one or more of diethylene glycol hexyl ether, diethylene glycol dibutyl ether, diethylene glycol monobutyl ether, diethylene glycol monooctyl ether, and tripropylene glycol butyl ether.

[0034] The present invention also discloses a method for preparing the aforementioned solder paste which can reduce the void rate by adding iodine element, comprising the following steps:

[0035] (1) Weigh rosin, thixotropic agent, activator, antioxidant, corrosion inhibitor and solvent according to proportion.

[0036] (2) Add rosin, solvent and thixotropic agent into the same container, heat to 150℃~170℃, and stir until completely melted.

[0037] (3) The above system is cooled to 120°C to 140°C, and then the activator, antioxidant and corrosion inhibitor are added and stirred until completely melted. The paste flux is obtained by cooling and stored in a cold storage at 0 to 10°C for later use.

[0038] (4) Weigh lead-free solder powder, flux and iodine additive in proportion, pour into a vacuum mixer, stir at a low speed for 15 to 20 minutes, then fill with nitrogen and stir at a medium speed for 50 to 60 minutes to fully mix the lead-free solder powder, flux and iodine additive, then evacuate and stir at a medium speed for 10 to 15 minutes to obtain solder paste.

[0039] The present invention is further described in detail below with multiple embodiments and comparative examples:

[0040] Embodiment 1:

[0041] This embodiment discloses a solder paste to which iodine is added to reduce the void rate, and is composed of the following raw materials in percentage by mass:

[0042] Lead-free solder powder 88%;

[0043] Flux 10%;

[0044] Iodine additive 2%;

[0045] The soldering flux is composed of the following raw materials in percentage by mass:

[0046]

[0047] The lead-free solder powder is composed of four elements: tin, bismuth, silver and copper, wherein the bismuth content is 15%, the copper content is 0.5%, the silver content is 4.5%, and the tin content is the balance. The iodine element additive is potassium iodide. The rosin is KHR-130 rosin crystal. The thixotropic agent is modified hydrogenated castor oil. The activator is succinic acid. The antioxidant is an organic acid antioxidant. The corrosion inhibitor is an organic corrosion inhibitor. The solvent is diethylene glycol hexyl ether.

[0048] This embodiment also discloses a method for preparing the aforementioned solder paste by adding iodine to reduce the void rate, comprising the following steps:

[0049] (1) Weigh rosin, thixotropic agent, activator, antioxidant, corrosion inhibitor and solvent according to proportion.

[0050] (2) Add rosin, solvent and thixotropic agent into the same container, heat to 155°C, and stir until completely melted.

[0051] (3) The system is cooled to 130°C, and then an activator, an antioxidant and a corrosion inhibitor are added and stirred until completely melted. The paste flux is obtained by cooling and stored in a cold storage at 5°C for later use.

[0052] (4) Weigh lead-free solder powder, flux and iodine additive in proportion, pour into a vacuum mixer, stir at low speed for 18 minutes, then fill with nitrogen and stir at medium speed for 55 minutes to fully mix the lead-free solder powder, flux and iodine additive, then evacuate and stir at medium speed for 12 minutes to obtain solder paste.

[0053] The solder paste prepared above was used to weld the methyl plate and the ethyl plate (the welding area was 6mm×6mm, which was a large-area welding). The upper surface of the methyl plate and the lower surface of the ethyl plate were electrically and mechanically connected by pulse reflow soldering. After solidification and cooling, a welding sample was obtained. The welding sample was tested using an X-ray machine, and the welding void rate obtained by the test was 4.3%.

[0054] Embodiment 2:

[0055] This embodiment discloses a solder paste to which iodine is added to reduce the void rate, and is composed of the following raw materials in percentage by mass:

[0056]

[0057] The soldering flux is composed of the following raw materials in percentage by mass:

[0058]

[0059] The lead-free solder powder is composed of four elements: tin, bismuth, silver and copper, wherein the bismuth content is 20%, the copper content is 0.8%, the silver content is 1%, and the tin content is the balance. The iodine element additive is a mixture of potassium iodide, sodium iodide, ammonium iodide, lithium iodide, zinc iodide, silver iodide and organic iodine compounds. The rosin is a mixture of KHR-130 rosin crystal, AX-80 fully hydrogenated rosin, maleic acid modified rosin, RJH-145 polymerized rosin and P-105 terpene resin. The thixotropic agent is a mixture of modified hydrogenated castor oil, organic bentonite and polyamide wax thixotropic agent. The activator is a mixture of succinic acid, glutaric acid, oxalic acid, phenylsuccinic acid, dodecanedioic acid and decyl tetradecanoic acid. The antioxidant is a mixture of organic acid antioxidants, phenolic antioxidants and thiol antioxidants. The corrosion inhibitor is a composite corrosion inhibitor. The solvent is a mixture of diethylene glycol hexyl ether, diethylene glycol dibutyl ether, diethylene glycol monobutyl ether, diethylene glycol monooctyl ether and tripropylene glycol butyl ether.

[0060] This embodiment also discloses a method for preparing the aforementioned solder paste by adding iodine to reduce the void rate, comprising the following steps:

[0061] (1) Weigh rosin, thixotropic agent, activator, antioxidant, corrosion inhibitor and solvent according to proportion.

[0062] (2) Add rosin, solvent and thixotropic agent into the same container, heat to 160°C, and stir until completely melted.

[0063] (3) The system is cooled to 135°C, and then an activator, an antioxidant and a corrosion inhibitor are added and stirred until completely melted. The paste flux is obtained by cooling and stored in a cold storage at 6°C for later use.

[0064] (4) Weigh lead-free solder powder, flux and iodine additive in proportion, pour into a vacuum mixer, stir at low speed for 15 minutes, then fill with nitrogen and stir at medium speed for 50 minutes to fully mix the lead-free solder powder, flux and iodine additive, then evacuate and stir at medium speed for 10 minutes to obtain solder paste.

[0065] The solder paste prepared above was used to weld the methyl plate and the ethyl plate (the welding area was 6mm×6mm, which was a large-area welding). The upper surface of the methyl plate and the lower surface of the ethyl plate were electrically and mechanically connected by pulse reflow soldering. After solidification and cooling, a welding sample was obtained. The welding sample was tested using an X-ray machine, and the welding void rate obtained by the test was 3.8%.

[0066] Embodiment 3:

[0067] This embodiment discloses a solder paste to which iodine is added to reduce the void rate, and is composed of the following raw materials in percentage by mass:

[0068] Lead-free solder powder 87%;

[0069] Flux 12%;

[0070] Iodine additive 1%;

[0071] The soldering flux is composed of the following raw materials in percentage by mass:

[0072]

[0073]

[0074] The lead-free solder powder is composed of four elements: tin, bismuth, silver and copper, wherein the bismuth content is 22%, the copper content is 1.2%, the silver content is 0.8%, and the tin content is the balance. The iodine element additive is sodium iodide. The rosin is AX-80 fully hydrogenated rosin. The thixotropic agent is organic bentonite. The activator is glutaric acid and oxalic acid. The antioxidant is a phenolic antioxidant. The corrosion inhibitor is an inorganic corrosion inhibitor. The solvent is diethylene glycol dibutyl ether.

[0075] This embodiment also discloses a method for preparing the aforementioned solder paste by adding iodine to reduce the void rate, comprising the following steps:

[0076] (1) Weigh rosin, thixotropic agent, activator, antioxidant, corrosion inhibitor and solvent according to proportion.

[0077] (2) Add rosin, solvent and thixotropic agent into the same container, heat to 150°C, and stir until completely melted.

[0078] (3) The system is cooled to 120°C, and then an activator, an antioxidant and a corrosion inhibitor are added and stirred until completely melted. The paste flux is obtained by cooling and stored in a cold storage at 0°C for later use.

[0079] (4) Weigh lead-free solder powder, flux and iodine additive in proportion, pour into a vacuum mixer, stir at a low speed for 19 minutes, then fill with nitrogen and stir at a medium speed for 52 minutes to fully mix the lead-free solder powder, flux and iodine additive, then evacuate and stir at a medium speed for 14 minutes to obtain solder paste.

[0080] The solder paste prepared above was used to weld the methyl plate and the ethyl plate (the welding area was 6mm×6mm, which was a large-area welding). The upper surface of the methyl plate and the lower surface of the ethyl plate were electrically and mechanically connected by pulse reflow soldering. After solidification and cooling, a welding sample was obtained. The welding sample was tested using an X-ray machine, and the welding void rate obtained by the test was 4.5%.

[0081] Embodiment 4:

[0082] This embodiment discloses a solder paste to which iodine is added to reduce the void rate, and is composed of the following raw materials in percentage by mass:

[0083] Lead-free solder powder 85%;

[0084] Flux 14%;

[0085] Iodine additive 1%;

[0086] The soldering flux is composed of the following raw materials in percentage by mass:

[0087]

[0088] The lead-free solder powder is composed of four elements: tin, bismuth, silver and copper, wherein the bismuth content is 25%, the copper content is 1%, the silver content is 2%, and the tin content is the balance. The iodine element additive is ammonium iodide. The rosin is maleic acid modified rosin. The thixotropic agent is a polyamide wax thixotropic agent. The activator is oxalic acid. The antioxidant is an organic acid antioxidant. The corrosion inhibitor is an organic corrosion inhibitor. The solvent is diethylene glycol monobutyl ether.

[0089] This embodiment also discloses a method for preparing the aforementioned solder paste by adding iodine to reduce the void rate, comprising the following steps:

[0090] (1) Weigh rosin, thixotropic agent, activator, antioxidant, corrosion inhibitor and solvent according to proportion.

[0091] (2) Add rosin, solvent and thixotropic agent into the same container, heat to 160°C, and stir until completely melted.

[0092] (3) The system is cooled to 140°C, and then an activator, an antioxidant and a corrosion inhibitor are added and stirred until completely melted. The paste flux is obtained by cooling and stored in a cold storage at 10°C for later use.

[0093] (4) Weigh lead-free solder powder, flux and iodine additive in proportion, pour into a vacuum mixer, stir at low speed for 20 minutes, then fill with nitrogen and stir at medium speed for 54 minutes to fully mix the lead-free solder powder, flux and iodine additive, then evacuate and stir at medium speed for 15 minutes to obtain solder paste.

[0094] The solder paste prepared above was used to weld the methyl plate and the ethyl plate (the welding area was 6mm×6mm, which was a large-area welding). The upper surface of the methyl plate and the lower surface of the ethyl plate were electrically and mechanically connected by pulse reflow soldering. After solidification and cooling, a welding sample was obtained. The welding sample was tested using an X-ray machine, and the welding void rate obtained by the test was 4.2%.

[0095] Embodiment 5:

[0096] This embodiment discloses a solder paste to which iodine is added to reduce the void rate, and is composed of the following raw materials in percentage by mass:

[0097] Lead-free solder powder 90%;

[0098] Flux 9.9%;

[0099] Iodine additive 0.1%;

[0100] The soldering flux is composed of the following raw materials in percentage by mass:

[0101]

[0102] The lead-free solder powder is composed of four elements: tin, bismuth, silver and copper, wherein the bismuth content is 18%, the copper content is 0.9%, the silver content is 3%, and the tin content is the balance. The iodine element additive is silver iodide. The rosin is RJH-145 polymerized rosin. The thixotropic agent is modified hydrogenated castor oil. The activator is dodecanedioic acid. The antioxidant is a thiol antioxidant. The corrosion inhibitor is an inorganic corrosion inhibitor. The solvent is diethylene glycol monooctyl ether.

[0103] This embodiment also discloses a method for preparing the aforementioned solder paste by adding iodine to reduce the void rate, comprising the following steps:

[0104] (1) Weigh rosin, thixotropic agent, activator, antioxidant, corrosion inhibitor and solvent according to proportion.

[0105] (2) Add rosin, solvent and thixotropic agent into the same container, heat to 170°C, and stir until completely melted.

[0106] (3) The system is cooled to 125°C, and then the activator, antioxidant and corrosion inhibitor are added and stirred until completely melted. The paste flux is obtained by cooling and stored in a cold storage at 7°C for later use.

[0107] (4) Weigh lead-free solder powder, flux and iodine additive in proportion, pour into a vacuum mixer, stir at low speed for 17 minutes, then fill with nitrogen and stir at medium speed for 60 minutes to fully mix the lead-free solder powder, flux and iodine additive, then evacuate and stir at medium speed for 13 minutes to obtain solder paste.

[0108] The solder paste prepared above was used to weld the methyl plate and the ethyl plate (the welding area was 6mm×6mm, which was a large-area welding). The upper surface of the methyl plate and the lower surface of the ethyl plate were electrically and mechanically connected by pulse reflow soldering. After solidification and cooling, a welding sample was obtained. The welding sample was tested using an X-ray machine, and the welding void rate obtained by the test was 4.4%.

[0109] Embodiment 6:

[0110] This embodiment discloses a solder paste to which iodine is added to reduce the void rate, and is composed of the following raw materials in percentage by mass:

[0111] Lead-free solder powder 89%;

[0112] Flux 10.5%;

[0113] Iodine additive 0.5%;

[0114] The soldering flux is composed of the following raw materials in percentage by mass:

[0115]

[0116] The lead-free solder powder is composed of four elements: tin, bismuth, silver and copper, wherein the bismuth content is 19%, the copper content is 0.7%, the silver content is 4%, and the tin content is the balance. The iodine element additive is an organic iodine compound. The rosin is P-105 terpene resin. The thixotropic agent is a polyamide wax thixotropic agent. The activator is decyl tetradecanoic acid. The antioxidant is a phenolic antioxidant. The corrosion inhibitor is a composite corrosion inhibitor. The solvent is tripropylene glycol butyl ether.

[0117] This embodiment also discloses a method for preparing the aforementioned solder paste by adding iodine to reduce the void rate, comprising the following steps:

[0118] (1) Weigh rosin, thixotropic agent, activator, antioxidant, corrosion inhibitor and solvent according to proportion.

[0119] (2) Add rosin, solvent and thixotropic agent into the same container, heat to 165°C, and stir until completely melted.

[0120] (3) The system is cooled to 128°C, and then the activator, antioxidant and corrosion inhibitor are added and stirred until completely melted. The paste flux is obtained by cooling and stored in a cold storage at 8°C for later use.

[0121] (4) Weigh lead-free solder powder, flux and iodine additive in proportion, pour into a vacuum mixer, stir at low speed for 16 minutes, then fill with nitrogen and stir at medium speed for 58 minutes to fully mix the lead-free solder powder, flux and iodine additive, then evacuate and stir at medium speed for 11 minutes to obtain solder paste.

[0122] The solder paste prepared above was used to weld the methyl plate and the ethyl plate (the welding area was 6mm×6mm, which was a large-area welding). The upper surface of the methyl plate and the lower surface of the ethyl plate were electrically and mechanically connected by pulse reflow soldering. After solidification and cooling, a welding sample was obtained. The welding sample was tested using an X-ray machine, and the welding void rate obtained by the test was 4.1%.

[0123] Comparative Example 1:

[0124] The difference between this comparative example and the above-mentioned Example 2 is that: in this comparative example, no iodine element additive is added, and a corresponding proportion of bromine element additive is added to the flux. The rest of the contents of this comparative example are the same as those of Example 2 and will not be repeated here.

[0125] The solder paste prepared above was used to weld the methyl plate and the ethyl plate (the welding area was 6mm×6mm, which was a large-area welding). The upper surface of the methyl plate and the lower surface of the ethyl plate were electrically and mechanically connected by pulse reflow soldering. After solidification and cooling, a welding sample was obtained. The welding sample was tested using an X-ray machine, and the welding void rate obtained by the test was 5.2%.

[0126] Comparative Example 2:

[0127] The difference between this comparative example and the above-mentioned Example 2 is that: in this comparative example, no iodine element additive is added, and a corresponding proportion of chlorine element additive is added to the soldering flux. The rest of the contents of this comparative example are the same as those of Example 2 and will not be repeated here.

[0128] The solder paste prepared above was used to weld the methyl plate and the ethyl plate (the welding area was 6mm×6mm, which was a large-area welding). The upper surface of the methyl plate and the lower surface of the ethyl plate were electrically and mechanically connected by pulse reflow soldering. After solidification and cooling, a welding sample was obtained. The welding sample was tested using an X-ray machine, and the welding void rate obtained by the test was 5.3%.

[0129] The design focus of the present invention is that by adding a specific content of iodine additives, the iodine additives can effectively reduce the surface tension of the solder paste, improve the wetting effect, and also accelerate the gas diffusion escape velocity, thereby achieving the purpose of reducing the void rate. There is no need to use a dedicated vacuum furnace, which effectively reduces the equipment cost. At the same time, this product does not contain bromine or chlorine, and no harmful gas will be generated during welding, which is very environmentally friendly.

[0130] The above description is only a preferred embodiment of the present invention and does not limit the technical scope of the present invention. Therefore, any slight modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A solder paste with iodine added to reduce void ratio, characterized in that: It is composed of the following raw materials in percentage by weight: Lead-free solder powder 85%~90%; Flux 9%~14%; Iodine additive 0.1% to 2%; The soldering flux is composed of the following raw materials in percentage by mass:

2. The solder paste with iodine added to reduce void ratio according to claim 1, characterized in that: The lead-free solder powder is composed of four elements of tin, bismuth, silver and copper, wherein the bismuth content is 15% to 25%, the copper content is 0.5% to 1.2%, the silver content is 0.8% to 4.5%, and tin is the balance.

3. The solder paste with iodine added to reduce void ratio according to claim 1, characterized in that: The iodine element additive is a mixture of one or more of potassium iodide, sodium iodide, ammonium iodide, lithium iodide, zinc iodide, silver iodide, and organic iodine compounds.

4. The solder paste with iodine added to reduce void ratio according to claim 1, characterized in that: The rosin is a mixture of one or more of KHR-130 rosin crystal, AX-80 fully hydrogenated rosin, maleic acid modified rosin, RJH-145 polymerized rosin, and P-105 terpene resin.

5. The solder paste with iodine added to reduce void ratio according to claim 1, characterized in that: The thixotropic agent is a mixture of one or more of modified hydrogenated castor oil, organic bentonite and polyamide wax thixotropic agent.

6. The solder paste with iodine added to reduce void ratio according to claim 1, characterized in that: The active agent is a mixture of one or more of succinic acid, glutaric acid, oxalic acid, phenylsuccinic acid, dodecanedioic acid, and decyltetradecanoic acid.

7. The solder paste with iodine added to reduce void ratio according to claim 1, characterized in that: The antioxidant is a mixture of one or more of organic acid antioxidants, phenolic antioxidants and thiol antioxidants.

8. The solder paste with iodine added to reduce void ratio according to claim 1, characterized in that: The corrosion inhibitor is an organic corrosion inhibitor, an inorganic corrosion inhibitor or a composite corrosion inhibitor.

9. The solder paste with iodine added to reduce void ratio according to claim 1, characterized in that: The solvent is a mixture of one or more of diethylene glycol hexyl ether, diethylene glycol dibutyl ether, diethylene glycol monobutyl ether, diethylene glycol monooctyl ether and tripropylene glycol butyl ether.

10. A method for preparing a solder paste with reduced void ratio by adding iodine as claimed in any one of claims 1 to 9, characterized in that: The following steps are included: (1) Weigh rosin, thixotropic agent, activator, antioxidant, corrosion inhibitor and solvent according to proportion; (2) Add rosin, solvent and thixotropic agent into the same container, heat to 150°C to 170°C, and stir until completely melted; (3) Cooling the above system to 120°C to 140°C, then adding the activator, antioxidant and corrosion inhibitor, and stirring until completely melted, cooling to obtain a paste flux, and storing it in a cold storage at 0 to 10°C for later use; (4) Weigh lead-free solder powder, flux and iodine additive in proportion, pour into a vacuum mixer, stir at a low speed for 15 to 20 minutes, then fill with nitrogen and stir at a medium speed for 50 to 60 minutes to fully mix the lead-free solder powder, flux and iodine additive, then evacuate and stir at a medium speed for 10 to 15 minutes to obtain solder paste.

Citation Information

Patent Citations

  • Halogen-free high-activity low-splatter solder wire soldering flux and preparing method thereof

    CN104191108A

  • Lead-free halogen-free tin paste and production process thereof

    CN104923952A

  • Soldering flux for lead-free solder hot air leveling

    CN106736040A

  • Novel lead-free tin paste and preparation method thereof

    CN109848603A

  • Novel welding material and application thereof

    CN110480206A

Cited By

  • Soldering flux, low-voidage high-lead soldering paste and preparation method of soldering flux

    CN121267469A

  • A soldering flux, a low-cavity high-lead soldering paste and a preparation method thereof

    CN121267469B